INTERAKSIONISME SIMBOLIK SANTRI TERHADAP KIAI MELALUI KOMUNIKASI DI PONDOK PESANTREN AL MUNAWWIR KLRAPYAK YOGYAKARTA - Alfajari, Muhammad Hamam (Informasi, 2016)
This research aims to determine the perspective of symbolic interactionism students to kiai in the communication process in Al Munawwir Islamic Boarding School Krapyak Yogyakarta. To achieve the objectives of the study, researchers used a qualitative approach, with qualitative descriptive type. The subjects in this study were students at Al Munawwir Boarding School Krapyak Yogyakarta. Data retrieval is done through interviews and observation. Results found is that symbolic interactionism students are not deterministic. That is, what is done by the students of the kiai is a subjective awareness of students who interpret certain symbols through interaction. The fact then that creates a social world for students. Social world that includes an appearance, gestures and symbolic language emerged in social situations, so in this context, the social world at the boarding school students can be said is a product of individuals as actors who are active